Enhancing EFL Young Learners' Speaking Ability through Buzz Group Technique: Evidence from an Indonesian Elementary School - Nuha, Muhammad Ulin; Huda, Khoirul; Khulel, Buyun (Lembaga Teewan Journal Solutions, 2026)
Speaking is an essential yet challenging skill for young English as a Foreign Language (EFL) learners because it requires linguistic knowledge, communicative competence, and self-confidence. This study aimed to examine the effectiveness of the Buzz Group Technique in improving the English speaking skills of sixth-grade students at MI Ma'arif NU Miru, Lamongan, Indonesia. A quantitative pre-experimental one-group pretest-posttest design was employed involving 18 students selected through total sampling. Data were collected using speaking performance tests assessing pronunciation, vocabulary, grammar, fluency, and comprehension, and analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the paired-samples t-test. The findings revealed a significant improvement in students' speaking performance, with the mean score increasing from 62.11 in the pretest to 80.06 in the posttest. The paired-samples t-test confirmed a significant difference between pretest and posttest scores (t(17) = −18.26, p < .001). All speaking components improved, with fluency showing the greatest gain. These findings indicate that the Buzz Group Technique is an effective student-centered strategy for enhancing English speaking skills and communicative competence among young EFL learners in Indonesian elementary schools.